Anthelmintic Activity of Annona squamosa - CHOUDHARY, G.P. (Asian Journal of Chemistry, 2010)
The aqueous extract of the leaves of Annona squamosa L. (Annonaceae) was evaluated for its anthelmintic efficacy in vitro. Graded doses of the extract (400, 800, 1200 μg/mL) showed significant anthelmintic activity, with their sensitivity when compared with the standard.